Electromagnetism for signal processing, spectroscopy and contemporary computing : fundamentals and applications /: fundamentals and applications. (2021) - Shah, Khurshed Ahmad; Kumbhani, Brijesh; Garcia-Sanchez, Raul F; Misra, Prabhakar, 1955-
No abstract available